Model planned abortion in Mexico City - Quintero Soto, María Luisa; Morales Flores, María de Lourdes (Revista de Investigación Académica Sin Frontera: Facultad Interdisciplinaria de Ciencias Económicas Administrativas - Departamento de Ciencias Económico Administrativas-Campus Navojoa, 2020)
Reproductive health policies, centered on the decriminalization of abortion, involve effects on beliefs, attitudes, intentions and behaviors of abortion. As women get older, education and income, rationally choose an abortion, but are far from ideal for procreation is 22 years old. The aim of this study is to establish the factorial structure of scales measuring four factors and 28 indicators (seven per factor) relating to the termination of pregnancy. Consequently, it conducted a non experimental, transversal and exploratory study with a nonrandom selection of 145 students. From a structural model ?? 2 = 346.57 (57gl) p = 0.000; CFI = 0.990; GFI = 0.995; RMSEA = 0.005; R 2 = 0,35?las intentions determined behavior (? = 0.64), but the factor solution was explained by beliefs (alpha = 0.781; 35% of the total variance explained). However, the context, the selection of the sample and the type of analysis prevents data generalize to other areas. It is recommended to perform a confirmatory factor analysis with a probabilistic sample selection in the population of the town.